PEMBUATAN MEMBRAN FOTOKATALITIK DARI SELULOSA DIASETAT SERBUK GERGAJI KAYU JATI (TECTONA GRANDIS L.F.) DAN TIO2 UNTUK PENGOLAHAN LIMBAH BAKU AIR PDAM - Fitriyatin najiyah (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2019)
Membrane technology is growing rapidlybecause of its superiority and has beenwidely applied in various industries. Thewaste of teak sawdust is increasing as thefurniture industry develops, but its utilizationis not optimal. The purpose of this study wasto determine the effect of the addition of TiO2on the mechanical properties andperformance of photocalytic membranesfrom cellulose diacetate teak sawdust forprocessing PDAM water raw materials.Cellulose isolation from teak sawdust wascarried out by adding NaOH 17.5% (b / v)and continued with cellulose bleachingprocess. Cellulose teak sawdust wassynthesized into cellulose diacetate byacetylation method. Membrane production isdone by phase inversion method withvariations in the composition of TiO2 0.25%,0.5%, 0.75% and 1% and also variations inevaporation time 20 seconds, 25 seconds,30 seconds and 35 seconds. The photocyticmembrane of cellulose diacetate from teaksawdust and TiO2 produced wascharacterized by thickness test, mechanicalproperties and performance. Photocalyticmembranes with optimum conditions arecharacterized by SEM (Scanning ElectronMicroscopy), FT-IR (Fourier TransformInfraRed) and antibacterial effectiveness.The optimum composition of thephotocatalytic membrane is 16% cellulosediacetate, 4% formamide, acetone 79% and1% TiO2 with 30 seconds evaporation time.The mechanical properties obtained werestress 1562,50000 kN / m2, strains 0.01 m /m and Young Modulus 141593,4835 kN /m2. The membrane has an averagethickness of 0.04 mm, a flux value of 683.10L.m2.hari-1, a rejection value of 97.74% andan antibacterial effectiveness of 99.57%.